Pengaruh Beban Kerja Terhadap Stres Kerja Pada Lembaga Kepolisian - Permatasari, Wahyuning Tyas; Alfira, Nadiya; Trisnawati, Vania; Aprilia, Jihan; Supriyadi, Tugimin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Work stress is an individual response in which a negative emotional state responds in the form of tension, psychological, physiological and behavioral responses or actions (stress reduction) which are used to adapt to the surrounding environment where threatening, stressful and dangerous events or occurrences occur. Workload is pressure that occurs because work demands are too much and must be completed in a short time. The method used in this research is a literature review which is used as a data source for writing this article, because it can help researchers to gain an understanding of workload and work stress. Researchers look for data sources according to the topic and reveal topics regarding workload and work stress, then analyze and conduct discussions. The results of analysis from several journal articles that have been carried out by previous researchers show that the workload of a police officer can influence the work stress that arises and this work stress can influence the performance of police officers who experience this, so it can be concluded between workload and work stress are related, and can have an influence on the performance of police officers in completing their work.